PENGARUH SANKSI PERPAJAKAN, PENGETAHUAN PAJAK, SIKAP WAJIB PAJAK, DAN TINGKAT EKONOMI TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DENGAN KONTROL PETUGAS KELURAHAN SEBAGAI VARIABEL MODERATING DI KOTA PEKANBARU - Winda Putri Ayunda; Nur Azlina; Azhari Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was aimed to examine the effect of tax penalties, tax knowledge, the attitude of taxpayer, and economic level to taxpayer compliance in paying Land and Building Tax which is moderating by the control officer urban village. This study used a sekunder data and primary data by distributed questionnaires of 120 exemplar to Taxpayer Land and Building in Pekanbaru. Of this amount, questionnaires received back was 109 exemplar (90,8%). Questionnaires that can not be processed as many as 9 exemplar (7,5%) because the quesionnaires has not been completed and can not be processed. So that 100 questionnaires (83,3%) has been completed and can be processed. Data analysis for hypothesis test was done with multiple regression analysis and moderated regression analysis (MRA). Result of this study give evidence that tax penalties and the attitude of taxpayer have not influence to taxpayer compliance in paying Land and Building Tax at significance level 5%. While the tax knowledge and economic level have significant influence to taxpayer compliance in paying Land and Building Tax at significance level 5%. On the other hand, the control officer urban village can strengthen the influence between tax penalties, tax knowledge, and economic level to the taxpayer compliance in paying Land and Building Tax at significance level 5%. However, the control officer actually weaken the influence between the attitude of taxpayer to taxpayer compliance in paying Land and Building Tax at significance level 5%.Keywords: Tax penalties, tax knowledge, the attitude of tax payer, economic level, tax payer compliance in paying Land and Buiding Tax, and control officer urban village.